RELATIONSHIP BETWEEN JOB SATISFACTION WITH PERFORMANCE OF EMPLOYEES IN COMPANY LEATHER MARGINING PROSPEROUS PROSPEROUS (MMS) YOGYAKARTA - Mursih, Tini; Lastari, SE, MM, Siwi; Darini, M. Si, Dra. Sri (Management, 2010)
The purpose of this study were (1) to determine whether there is a relationship between job satisfaction with the performance of employees in the Company Leather Margining Mkamur Yogyakarta Sejahtera, (2) to determine whether there is correlation between communication with colleagues and superiors on job satisfaction in the Company Leather Margining Makmur Sejahtera . The problem in this study is whether there is a relationship between job satisfaction with the performance of employees in the Company Margining Makmur Sejahtera Yogyakarta. Data collection methods use questionnaires or questionnaire. In this study the number of respondents as many as 50 people were employees of the Company Margining Makmur prosperous Yogyakarta. As for the method of data analysis used Pearson product moment correlation. Because of this correlation can be used to find out how the relationship of job satisfaction with the performance of employees under investigation. Keywords: Employees, Job Satisfaction.